USING QUANTUM-CHEMICAL PARAMETERS FOR PREDICTING ANTIRADICAL (HO•) ACTIVITY OF RELATED STRUCTURES CONTAINING A CINNAMOIL FRAGMENT. IV. STRUCTURE-ACTIVITY RELATIONSHIP BETWEEN UNSATURATION INDICES AND FLAVONE DERIVATIVES WITH FLOROGLUCIN RING “A” - E. T. Oganesyan; S. S. Shatokhin (Фармация и фармакология (Пятигорск))
The quantum-chemical parameters of 52 derivatives related to flavanones, flavanonoles, flavones and flavonoles with a phloroglucinic type of the A ring and containing electron-donating substituents in the B ring were studied.The aim is the analysis of the dynamics of changes in the electron density, bond numbers, free valence indices and unsaturation indices on carbon atoms C-7 → C-8 of the vinyl group of the main conjugation chain in relation to the position and number of substituents in the “B” ring and the type of the pharmacological activity.Materials and methods. The quantum-chemical parameters of the 4 analyzed groups of the compounds, have been calculated by the semi-empirical method PM7 (WinMopac 2016 program) on the workstation with an Intel Xeon E5-1620 3.5 GHz processor, 20 GB of RAM.Results and discussion. When comparing the quantum chemical parameters of the analyzed compounds, it was established that when the C-7 → C-8 multiple bond is formed, the free valency and unsaturation indices increase on both carbon atoms of the vinylene group in flavones and flavonols compared to the corresponding flavanones and flavanonols. This is explained by the fact that the value of the bond numbers Nµ on these atoms, on the contrary, decreases (Fµ = 4.732-Nµ). The transition from flavanone to flavone is accompanied by the formation of a vinyl group C-7 → C-8, and therefore both atoms from the sp3-hybridized state go into the sp2-state. The consequence of this transformation is a change in the electronegativity value and an increase in the unsaturation index of C-7 and C-8 atoms: C sp3 = 2.5;  Csp2 = 2.8. At the same time, the transition from flavanone to flavone leads to the formation of a conjugated system with the participation of π-electrons of the aromatic system “B”, C-7, C-8 atoms and the carbonyl group, which is commonly called the “main conjugation chain”. These structural changes, namely, the transition from a less oxidized flavanone to a more oxidized flavone, contribute to a decrease in the electron density on C-7 and C-8 atoms, and an increase in the total unsaturation of the molecules in general. Mulliken charges on C-7 of all groups of compounds are characterized by a positive value. As for the carbon atoms of the B fragment, the following features are revealed here: in the presence of one substituent -OH or -OCH3 on the carbon atom to which the substituent is bounded, the Mulliken charge is positive; if there are two substituents in the B ring -OH or -OCH3, as well as two -OCH3 groups, then the carbon atoms bonded to the indicated substituents also have a positive Mulliken charge; in the case of trihydroxy substituted in the C-2, C-3 and C-4 B ring, all three carbon atoms are characterized by a positive Mulliken charge; if there are methoxy groups in positions C-2, C-3 and C-4, then the positive Mulliken charge is concentrated only on C-2 and C-4 atoms, and on C-3 atom this charge has a negative value.Conclusion. The above data on the quantum-chemical parameters of the main conjugation chain indicate that the transition of C-7 and C-8 atoms to the sp2-hybrid state, leads to a decrease in the electron density and a decrease in the bond numbers, with a simultaneous increase in the indices of unsaturation and free valence on these atoms. Thus, the trigger mechanism of the anti-radical activity, primarily with respect to the HO • radical, is determined by the fact that this particle, electrophilic in its properties, will attach in the C-8  atom during an initial attack.